2a-8+4=45-5a 2a-4=45-5a 2a-4+4=45+4-5a 2a+5a=49-5a+5a 7a=49 / by 7 = A=7
6a + 5a = -11 Combining like terms: 11a = -11 Dividing by 11: a = -1
To solve the equation 5a + 5 = 6a - 7, you first want to simplify both sides. Start by combining like terms on each side of the equation. Add 7 to both sides to isolate the variable terms on one side. Then, subtract 5a from both sides to solve for the variable a. The final answer is a = 12.
12b-4
3a x 2a =24
It is not an equation but an algebraic expression that can be simplified to: 12b-5a
If your referring to addition, then it would be 8a+14b. If your multiplying it would be, 15a*24b simplified to 360ab.
6a + 4 = 5a - 2 means that 6a - 5a = -2 - 4 which gives a = -6
Oh, come on! 6a - 5a = a, 7 - 5 = 2
If: 2a+13 = 5a+1 Then: a = 4
2a-8+4=45-5a 2a-4=45-5a 2a-4+4=45+4-5a 2a+5a=49-5a+5a 7a=49 / by 7 = A=7
5a + 2 = 7 subtract 2 from both sides: 5a = 5 divide both sides by 5: a = 1
-59
6a + 5a = -11 Combining like terms: 11a = -11 Dividing by 11: a = -1
2x+a=p 2x=p-a x=.5p-.5a
-9/4b -10/3b =-67/6 9/4b +10/3b = 67/6 27/12b + 40/12b = 67/6 67/12b =67/6 12b = 6 b = 6/12 b=1/2
12b-4